A COMPARATIVE STUDY BETWEEN THE PRESENCE OR ABSENCE OF SUPPORT FOR FARMERS OF THE CORN CROP IN IRAQ FOR THE YEAR 2019 - L. K. ALJanabi; N. S. Habib; M. K. Farhan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Using the policy of price has a significant impact to developing the production of a particular crop by increasing productivity, which is eventually reflected in achieving high rates of self-sufficiency of the crops. The research objective is to identify the most important economic and social effects that will result from cancelling or reducing this subsidy Using the Cost-Benefit Analysis. The results showed that the ratio of return to cost in the case of reducing subsidies for corn farmers about 0.92%, which indicates that the one dinar invested in the cultivation of the corn under the subsidy policy achieves about 0.92 dinar, which is higher than the ratio of return to costs In the absence of this policy, that reached 0.65%. This indicates that the subsidy policy, even in reducing it, will lead to a reduction in farmers’ losses by 27%. This is an incentive for the government to continue providing support to farmers to continue the production process. The study recommended that there is necessarily need to reorganize the strategy of providing support to farmers and find appropriate mechanisms for implementing the government policy to ensure that all corn farmers benefit from this support.